THE IMPACT OF INFLATION AND REAL INTEREST RATES IN SAUDI ARABIA ON THE SAR/SDR EXCHANGE RATES - Mishaal Abdulaziz Alkhudair; Shabir Hakim (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Many factors influence the exchange rate; this study will attempt to examine two of these factors, inflation and interest rates. This study is concerned with assessing the extent and the nature of the impact of inflation and interest rates in Saudi Arabia on the SAR/SDR exchange rate, to which the study hypothesized that there would be a negative relationship between inflation and the exchange rate and a positive relationship between the interest rates and the exchange rate. A regression analysis was used to on the monthly SAR/SDR exchange rate, inflation, and interest rates for the period ranging from January 2004 to September 2015. The study has found that there is a significant relationship between the SAR/SDR exchange rate and inflation, while there is no significant relationship between the exchange rate and interest rates, furthermore the finding has also confirmed the hypotheses of the study. The finding could have important implications that would assist in making well-informed and more prudent investment and financing decisions.